Myiasis in an 89-year-old man with non-hodgkin lymphoma. - Afshin Mohammad Alizadeh; Nasim Zamani (Tehran University of Medical Sciences, 2014)
Myiasis is due to the opportunistic dipterous larvae feeding on viable or necrotic tissues of the host occurring throughout the world. We report a case of oral myiasis in an immune-compromised patient suffering from nonHodgkin lymphoma. We  would like  to  emphasize that such ectoparasitic infections may happen in  immuno- compromised patients and oral hygiene should be evaluated in all of these patients.